Budaya Organisasi dan Tantangan Globalisasi - Pasuhuk, Lefrand Sermon (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
An organization’s culture is formed by the founder of the organization as meaning together to enhance the progress and effectiveness of a company.  Much evidence suggests that a strong culture of an organization has led the organization in a better success rate.  But in this era of globalization, as now, there are challenges facing the organization, which could affect the culture of an organization.  With the disappearance of borders between countries, facilitate the entry of the culture of the countries (developed countries) to other countries.  This is also true for an organization.  Cultural organizations have been formed would be a challenge due to organization.  Cultural organization formed to improve corporate performance an corporate activities will be more effective.  Organizations wherever it operates, will not be separated from the influence of globalization.  If the organization does not anticipate the rapid cultural changes coused by globalization, the globalization that is what will destroy the culture of an organization.